Law as a Social Controlling Agent in Society from a Sociological View of Law - Rossita Trijaya Novia; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law as a social controlling agent plays an active role as something capable of determining human behavior that deviates from legal rules. So that the law can provide sanctions for violators. Humans themselves as legal subjects in social relations are also inseparable from the natural nature of humans who are also capable of making mistakes, both of which ultimately harm themselves or others. Therefore law as a social controlling agent in terms of legal sociology theory has an important role in people's lives. In order to achieve justice, legal certainty, order in people's lives, the law must be upheld. The concept of law enforcement is inseparable from the purpose of law which wants to form a younger and prosperous society.